2008
DOI: 10.2110/palo.2007.p07-035r
|View full text |Cite
|
Sign up to set email alerts
|

Geobiological Aspects of the Earliest Triassic Microbialites Along the Southern Periphery of the Tropical Yangtze Platform: Initiation and Cessation of a Microbial Regime

Abstract: Microbialite masses within the lowest Triassic strata along the southern periphery of the tropical Yangtze Platform were produced in a post-Permian microbial regime. These microbialites (the Hindeodus parvus Zone), which are represented by thrombolites, occur only where terrigenous sediment influx was rare, even in shallow-marine settings. The lower parts of the thrombolites lie upon a distinctly unconformable Permian-Triassic boundary and exhibit a thinbedded to thick-bedded planar structure. In contrast, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 62 publications
7
98
1
Order By: Relevance
“…Many previous studies have also documented the presence of very small (b0.05 mm) coccoid fossils in these microbialites (Ezaki et al, 2003(Ezaki et al, , 2008Wang et al, 2005;Yang et al, 2011;Kershaw et al, 2012), and related them to cyanobacteria. Some researchers (Ezaki et al, 2003) suggested that the precursor microbes of the coccoid fossils formed the mesoclots constituting the microbialites.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Many previous studies have also documented the presence of very small (b0.05 mm) coccoid fossils in these microbialites (Ezaki et al, 2003(Ezaki et al, , 2008Wang et al, 2005;Yang et al, 2011;Kershaw et al, 2012), and related them to cyanobacteria. Some researchers (Ezaki et al, 2003) suggested that the precursor microbes of the coccoid fossils formed the mesoclots constituting the microbialites.…”
Section: Introductionmentioning
confidence: 74%
“…It is generally 2 to 10 m thick and consists of two parts (Kershaw et al, 1999(Kershaw et al, , 2007(Kershaw et al, , 2012Lehrmann, 1999;Ezaki et al, 2003Ezaki et al, , 2008Wang et al, 2005Wang et al, , 2012Jiang and Wu, 2007a,2007bYang et al, 2011). The lower part consists of gray limestone with scattered irregular brown spots 0.5 to 1.5 cm wide, and has been described as spotted rock.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The models for their generation consist of a series of viewpoints, including: (1) reduced benthic grazing pressure; (2) upwelling of anoxic alkaline waters; (3) elimination of skeletal CaCO 3 sinks; (4) increased nutrient levels from erupted volcanic ash; and (5) a rebound in carbonate saturation following a transient ocean acidification event (Lehrmann et al 2015 and references therein). The upwelling model, in particular, has been applied by numerous workers in the Early Triassic (Kershaw et al 1999;Ezaki et al 2003;Lehrmann et al 2003;Pruss and Bottjer 2004;Pruss et al 2005;Kershaw et al 2007Kershaw et al , 2009Kershaw et al , 2011Ezaki et al 2008;Mary and Woods 2008;Mata and Bottjer 2011;He et al 2013;Woods 2014). Lehrmann et al (2003) also drew attention to the possibility of PTBM formation in oxygenated seawater conditions.…”
Section: Introductionmentioning
confidence: 99%